Diagnostic significance of the novel biomarker combination for early-stage non-small cell lung cancer detection: results of the blind clinical study - Tcherkassova, Janneta; Klinski, Evgueni; Tsurkan, Sergey; Prostyakova, Anna; Boroda, Alexander; Pirogova, Yuliya N.; Bagmet, Leonid N.; Sekacheva, Marina (Frontiers in Oncology, 2025)
BackgroundNSCLC can be cured in up to 65% of cases if detected early. However, most of the lung cancer (LC) cases are diagnosed at an advanced stage.ObjectiveThe assessment of various tumor markers in retrospective double-blind clinical study and their possible combinations for detection of early-staged non-small cell lung cancer (NSCLC); evaluation of the best TM panel as a pre-screening tool for LC before Low-Dose CT scan; the development of the protocol for future prospective clinical study.MethodsA double-blind clinical study was conducted on 304 clinically verified patients, including 141 NSCLC, 133 healthy volunteers and 30 patients with COPD. Quantitative measurement of various TM was carried out using commercial immunoassays.ResultsUnlike other tumor markers, which are expressed proportionally to the tumor growth, CA-62 demonstrated the highest values at Stage I and II of NSCLC. The use of CA-62 for early-staged NSCLC achieves 92% sensitivity at 95% specificity (AUC = 0.973). The diagnostic value of the best TM signature (CA-62, CEA and CYFRA 21-1): 100% Specificity, 90% Sensitivity, and 94% test accuracy, AUC=0.990.ConclusionsThe results of the study demonstrated that the TM combination allows increasing the Specificity for patients with indeterminate pulmonary nodules detected by CT scans and improves the accuracy of differential diagnosis.